Impact of Mycotoxins on Animals’ Oxidative Status - Mavrommatis, Alexandros; Giamouri, Elisavet; Tavrizelou, Savvina; Zacharioudaki, Maria; Danezis, George; Simitzis, Panagiotis E.; Zoidis, Evangelos; Tsiplakou, Eleni; Pappas, Athanasios C.; Georgiou, Constantinos A.; Feggeros, Kostas (Antioxidants, 2021)
Mycotoxins appear to be the “Achilles’ heel” of the agriculture sector inducing enormous economic losses and representing a severe risk to the health of humans and animals. Although novel determination protocols have been developed and legislation has been implemented within Europe, the side effects of mycotoxins on the homeostatic mechanisms of the animals have not been extensively considered. Feed mycotoxin contamination and the effects on the antioxidant status of livestock (poultry, swine, and ruminants) are presented. The findings support the idea that the antioxidant systems in both monogastrics and ruminants are challenged under the detrimental effect of mycotoxins by increasing the toxic lipid peroxidation by-product malondialdehyde (MDA) and inhibiting the activity of antioxidant defense mechanisms. The degree of oxidative stress is related to the duration of contamination, co-contamination, the synergetic effects, toxin levels, animal age, species, and productive stage. Since the damaging effects of MDA and other by-products derived by lipid peroxidation as well as reactive oxygen species have been extensively studied on human health, a more integrated monitoring mechanism (which will take into account the oxidative stability) is urgently required to be implemented in animal products.